Bigfoot boy. [2], The unkindness of ravens - Torres, J., 1969- (Kids Can Press, 2013)
Another weekend at Grammy's, another weekend of Rufus using his magic totem to transform himself into Bigfoot Boy! But when you're big, hairy and loud, it's hard to keep your powers a secret, especially when there are trickster ravens that want the magic for themselves. You won't want to miss this second rrrawesome adventure of Bigfoot Boy and his friends!